Researcher’s perspectives on halal supply chain management: definition and methodology - Abd Kadir, Muhammad Hijrah; Raja Mohd Rasi, Raja Zuraidah; Omar, Siti Sarah; Ahmad, Md Fauzi; Mohd Nawi, Nazri; Abdul Manap, Zariq Imran; Saguna, Baharundin (American Scientific Publishers, 2018)
The Halal Industry is still in the stage of development and empowerment practices. The efforts to conduct the way forward in compliance with Islamic perspective (Shariah Laws) and desirable and necessary along the world. One of the problems facing the global halal industry is the lack of recognition halal certified products are viewed by Muslims as a mark of quality by the different halal certification bodies. With the diverse increasing demand towards halal food throughout the world but the integration of halal practices into supply chain processes in the under lacking coverage. The objective of this paper is to give a basic information in the definition of halal from the Shariah perspective and the researcher’s methodology used in their past research. The references from this desktop working research are allocate from the past research on halal supply chain management. By having the clear definition and methodology, the paper will conclude the easy way for others researcher to get clear understanding about the definition of halal and the other method using in the future studies.